2015
DOI: 10.18502/kls.v2i1.179
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENCY OF COPPER-RESISTANT BACTERIA Cupriavidus sp. IrC4 ISOLATED FROM INDUSTRIAL WASTEWATER TREATMENT PLANT IN RUNGKUT-SURABAYA AS A BIOREMEDIATION AGENT FOR HEAVY METALS

Abstract: <p>Cupriavidus sp. IrC4 is a copper-resistant bacteria isolated from activated sludge in an Industrial Wastewater Treatment Plant in Rungkut-Surabaya, Indonesia. The purpose of this research was to study the potency of Cupriavidus sp. IrC4 as a bioremediation agent for copper, lead, mercury, and cadmium. Resistance of Cupriavidus sp. IrC4 to heavy metals were determined by measuring the minimum inhibitory concentration (MIC). Accumulation of copper, cadmium, and lead were determined by Atomic Absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Meanwhile, Acinetobacter sp. IrC2 isolated from industrial sewage, Rungkut-Indonesia demonstrated multiple resistance to copper, cadmium, mercury, lead, and zinc (Irawati et al 2015).…”
Section: Isolation and Characterization Of Copper-resistant Bacteriamentioning
confidence: 99%
“…Meanwhile, Acinetobacter sp. IrC2 isolated from industrial sewage, Rungkut-Indonesia demonstrated multiple resistance to copper, cadmium, mercury, lead, and zinc (Irawati et al 2015).…”
Section: Isolation and Characterization Of Copper-resistant Bacteriamentioning
confidence: 99%
“…Appropiate concentration of heavy metal stock solution was added in autoclaved medium. LB agar was made with an addition of 2% pure agar (Irawati et al 2015).…”
Section: Growth Mediummentioning
confidence: 99%
“…IrC1 and Acinetobacter sp. IrC2 were facilitated through the bioaccumulation of copper inside the cell up to 364.66 mg · L −1 of copper [16] It also was reported that the bacterium removed copper up to 52.98 % [24]. Previous studies showed that bacterial inoculation enhanced the ability of E. Crassipes to accumulate heavy metal.…”
Section: Copper Removalmentioning
confidence: 97%